Mating plugs and sexual cannibalism : variations between populations of the neotropical spider Leucauge mariana (2017)
"Geographic distribution and its interconnected biotic and abiotic factors, may favor variation in the expression of sexual displays. In Leucauge orb web spiders females participate in mating plugs formation and use them as tools of cryptic female choice after the evaluation of male performance during courtship and mating. Our aim was to assess and compare sexual behavior and mating plug formation in two populations of Leucauge mariana, one from Costa Rica (CR) and from Colombia (CO). For that purpose, we carried out mating trials in order to describe in detail courtship and mating behavior of sexual pairs from the CO population and we compared the results with data available from pairs from CR population. In addition, we assessed in males from CO if characteristics such as the amount of the sperm transferred during mating may influence plug formation". -- Tomado del resumen.